The Effect of Cigarette Smoking on Bone Healing in Elderly Individuals with Colle's Fracture - Sadeq A. Al-Mukhtar (SAGE Publishing, 2010)
Background Elderly men and women who smoke for many years are more likely to sustain fractures after minimal trauma than are nonsmokers. The two major risk factors for fractures are low bone mineralization density (BMD) and a propensity for falling in smokers known to have poorer neuromuscular function compared with nonsmokers. Smokers are weaker and have poorer balance, gait, and integrated physical function. Older people who smoke cigarettes have significantly lower BMD than those who do not. Cadaveric studies show that a decrease of BMD by 10% results in decrease of bone strength by three-fold. Thus, it is reasonable to expect an increased incidence of fractures among smokers on the basis of BMD level alone. Aim The aim of the study is to find the effects of cigarettes smoking on the time of healing in comparison with nonsmoker patients with colles fracture. Patients and Methods A cross-sectional study was done in AlKindy Teaching Hospital, AlKarkh General Hospital, and AlJarah Private Hospital in the period between March 1999 and February 2006. 280 patients with colles fracture were included and divided into two groups (smokers and nonsmokers). Age, sex, causes of the trauma type of the fracture, number of cigarettes smoking, body mass index, time of healing and others were studied. Results Group A • Male to female ratio was 1:2.29. • The commonest age group was between (60-69) years 64.3%. • Body mass index (BMI), 50% of patients were within 20-24 score and 25% were within 25-29 score. • The type of fracture was 86.6% displaced fracture. • The time of healing was 61.6% within 4 weeks and 33.93% healed within 5-6 weeks. Group B • Male to female ratio was 1:2.36. • The commonest age group was 50-59 years 52.4. • The type of fracture was 86.9% displaced. • Regarding BMI, 51.2% of patients were within score less than 20, and 34.5% were within 20-40 score. • The time of healing was 67.3% within 5-6 weeks and 18.5% healed within 4 weeks. Conclusion Cigarette smoking increases the time of healing in elderly individuals with colles fracture.